A Review of Climate Change and Agro-industrial Development in Cameroon - Yaouba, Bassirou; Dieudonné, Bitondo (Environmental Protection Research, 2022)
Climate change influences the performance of Cameroon's agribusinesses. Therefore, Cameroon was considered one of the countries most exposed to climate risks. The most vulnerable sector of its economy remains agriculture, which provides raw materials essential to the development of agribusinesses. This paper addressed the issue of climate change and its influences on the development of the country’s agribusiness. The methodological approach was based on bibliometric and bibliographic analyses, with a critical reading of articles published between 2005 and 2020 using search engines such as Microsoft Academic, Web of Science, Scopus, Google Scholar, and ResearchGate. The results of the literature review showed that climate change is a serious threat to the development of Cameroon's agro-industries. Observations revealed variability in rainfall and temperature and an increase in extreme weather events. Climate variability would then lead to a 15% reduction in crop yields, on average, in sub-Saharan Africa in general by 2046 to 2055 compared to 1996 to 2005. From 2005 to 2020, the number of scientific publications in the field of climate change amounted to 215,470, including 127,379 on climate change and agribusiness. The yield reduction shows that climate change is a serious threat to agribusiness development, and the number of scientific publications shows a growing interest in this issue. Mitigation measures focused on the development of both climate monitoring tools and resilience strategies.